On the coupling between the dynamics of protein and water. Issue 12 (9th March 2017) - Gavrilov, Yulian; Leuchter, Jessica D.; Levy, Yaakov
Abstract : The solvation entropy of flexible protein regions is higher than that of rigid regions and contributes differently to the overall thermodynamic stability. Abstract : Interactions between water and biomolecules can significantly change the former's structural, dynamic, and thermodynamic properties relative to the bulk. Experimental, theoretical, and computational studies show that changes in water properties can be observed at distances of more than 10 Å from a biomolecule. The effects of biopolymers on hydration water molecules can be attributed to several factors: the chemical nature of the amino acid residues involved, the spatial arrangement of the biomolecule, and its conformational flexibility. In the current study, we concentrate on the effect of protein chain flexibility on the properties of hydration water, using short peptides as a model. We constructed 18 linear peptides with the sequence (XXGG) × 5, where X represents one of the common amino acids, other than glycine and proline. Using molecular dynamics (MD) simulations, we studied how restricting the chain flexibility can affect the structural, dynamic, and thermodynamic properties of hydration water. We found that restricting the peptide dynamics can slow down the translational motions of water molecules to a distance of at least 12–13 Å. Analysis of the 'slow' water molecules (residence time ≥ 100 ps) together with a thermodynamic analysis of water within 4.5 Å of the peptide revealed significant differences between the hydration properties of the peptides. The balance between the entropic and enthalpic solvation effects defines the final contribution to the hydration free energy of the restricted system. Our study implies that different regions of the proteins that have different configurational entropies may also have different solvation entropies and therefore different contributions to the overall thermodynamic stability. Therefore, mutations of a solvent exposed residue may modify the thermodynamic stability depending solely on the flexibility of the mutated sites due to their different solvation characteristics.